Core‐binding factor acute myeloid leukemia with t(8;21): Risk factors and a novel scoring system (I‐CBFit). (16th August 2018) - Ustun, Celalettin; Morgan, Elizabeth; Moodie, Erica E. M.; Pullarkat, Sheeja; Yeung, Cecilia; Broesby‐Olsen, Sigurd; Ohgami, Robert; Kim, Young; Sperr, Wolfgang; Vestergaard, Hanne; Chen, Dong; Kluin, Philip M.; et al.
Abstract: Background: Although the prognosis of core‐binding factor (CBF) acute myeloid leukemia (AML) is better than other subtypes of AML, 30% of patients still relapse and may require allogeneic hematopoietic cell transplantation (alloHCT). However, there is no validated widely accepted scoring system to predict patient subsets with higher risk of relapse. Methods: Eleven centers in the US and Europe evaluated 247 patients with t(8;21)(q22;q22). Results: Complete remission (CR) rate was high (92.7%), yet relapse occurred in 27.1% of patients. A total of 24.7% of patients received alloHCT. The median disease‐free (DFS) and overall (OS) survival were 20.8 and 31.2 months, respectively. Age, KIT D816V mutated (11.3%) or nontested (36.4%) compared with KIT D816V wild type (52.5%), high white blood cell counts (WBC), and pseudodiploidy compared with hyper‐ or hypodiploidy were included in a scoring system (named I‐CBFit). DFS rate at 2 years was 76% for patients with a low‐risk I‐CBFit score compared with 36% for those with a high‐risk I‐CBFit score ( P < 0.0001). Low‐ vs high‐risk OS at 2 years was 89% vs 51% ( P < 0.0001). Conclusions: I‐CBFit composed of readily available risk factors can be useful to tailor the therapy of patients, especially for whom alloHCT is not need in CR1 (ie, patients with a low‐risk I‐CBFit score). Abstract : CBF AML is relatively favorable AML; however, 30%‐40% of patients still relapse. There is no widely used scoring system to identify high‐risk patients. We here developed a novel scoring system (I‐CBFit) can differ patients with high risk of treatment failure from this with a lower risk score. This scoring system can be very useful to prognosticate and thus to choose right therapy (eg, personalize therapy) in CR1.